Acute-on-chronic: using magnetic resonance imaging to disentangle the haemodynamic responses to acute and chronic fetal hypoxaemia - Darby, Jack R. T.; Saini, Brahmdeep S.; Holman, Stacey L.; Hammond, Sarah J.; Perumal, Sunthara Rajan; Macgowan, Christopher K.; Seed, Mike; Morrison, Janna L. (Frontiers in Medicine, 2024)
Introduction The fetal haemodynamic response to acute episodes of hypoxaemia are well characterised. However, how these responses change when the hypoxaemia becomes more chronic in nature such as that associated with fetal growth restriction (FGR), is less well understood. Herein, we utilised a combination of clinically relevant MRI techniques to comprehensively characterize and differentiate the haemodynamic responses occurring during acute and chronic periods of fetal hypoxaemia. Methods Prior to conception, carunclectomy surgery was performed on non-pregnant ewes to induce FGR. At 108–110 days (d) gestational age (GA), pregnant ewes bearing control (n = 12) and FGR (n = 9) fetuses underwent fetal catheterisation surgery. At 117–119 days GA, ewes underwent MRI sessions where phase-contrast (PC) and T2 oximetry were used to measure blood flow and oxygenation, respectively, throughout the fetal circulation during a normoxia and then an acute hypoxia state. Results Fetal oxygen delivery (DO2) was lower in FGR fetuses than controls during the normoxia state but cerebral DO2 remained similar between fetal groups. Acute hypoxia reduced both overall fetal and cerebral DO2. FGR increased ductus venosus (DV) and foramen ovale (FO) blood flow during both the normoxia and acute hypoxia states. Pulmonary blood flow (PBF) was lower in FGR fetuses during the normoxia state but similar to controls during the acute hypoxia state when PBF in controls was decreased. Conclusion Despite a prevailing level of chronic hypoxaemia, the FGR fetus upregulates the preferential streaming of oxygen-rich blood via the DV-FO pathway to maintain cerebral DO2. However, this upregulation is unable to maintain cerebral DO2 during further exposure to an acute episode of hypoxaemia. The haemodynamic alterations required at the level of the liver and lung to allow the DV-FO pathway to maintain cerebral DO2, may have lasting consequences on hepatic function and pulmonary vascular regulation after birth.